# CROSS PRODUCT RULE IN PROPORTION

Problem 1 :

Solution:

Use Cross Product Rule,

9x = 5(x + 2)

9x = 5x + 10

9x - 5x = 10

4x = 10

x = 10/4

x = 2.5

Problem 2 :

Solution:

Use Cross Product Rule,

3n = 8(n - 4)

3n = 8n - 32

5n = 32

n = 32/5

n = 6.4

Problem 3 :

Solution:

Use Cross Product Rule,

10a = 3(a + 2)

10a = 3a + 6

10a - 3a = 6

7a = 6

a = 6/7

Problem 4 :

Solution:

Use Cross Product Rule,

2(x + 1) = 9(x + 2)

2x + 2 = 9x + 18

2x - 9x = 18 - 2

-7x = 16

x = -16/7

Problem 5 :

Solution:

Use Cross Product Rule,

9(v - 5) = 4(v + 6)

9v - 45 = 4v + 24

9v - 4v = 24 + 45

5v = 69

v = 69/5

v = 13.8

Problem 6 :

Solution:

Use Cross Product Rule,

4(n + 8) = 10(n - 9)

4n + 32 = 10n - 90

4n - 10n = -90 - 32

-6n = -122

n = 122/6

n = 61/3

Problem 7 :

Solution:

Use Cross Product Rule,

7(x - 6) = 4(x - 1)

7x - 42 = 4x - 4

7x - 4x = 42 - 4

3x = 38

x = 38/3

Problem 8 :

Solution:

Use Cross Product Rule,

5(k + 5) = 8(k - 6)

5k + 25 = 8k - 48

5k - 8k = -48 - 25

-3k = -73

k = 73/3

Problem 9 :

Solution:

Use Cross Product Rule,

(x + 5)(x - 2) = 30

x2 - 2x + 5x - 10 = 30

x2 + 3x - 10 = 30

x2 + 3x - 10 - 30 = 0

x2 + 3x - 40 = 0

(x + 8)(x - 5) = 0

x = -8 or x = 5

Problem 10 :

Solution:

Use Cross Product Rule,

(x - 3)(x + 5) = 20

x2 + 5x - 3x - 15 = 20

x2 + 2x - 15 - 20 = 0

x2 + 2x - 35 = 0

(x - 5)(x + 7) = 0

x = 5 or x = -7

Problem 11 :

Solution:

Use Cross Product Rule,

(m + 3)(m - 4) = 44

m2 - 4m + 3m - 12 = 44

m2 - m - 12 = 44

m2 - m - 12 - 44 = 0

m2 - m - 56 = 0

(m - 8)(m + 7) = 0

m = 8 or m = -7

Problem 12 :

Solution:

Use Cross Product Rule,

(x - 5)(x - 1) = 32

x2 - x - 5x + 5 = 32

x2 - 6x + 5 - 32 = 0

x2 - 6x - 27 = 0

(x - 9)(x + 3) = 0

x = 9 or x = -3

Problem 13 :

Solution:

Use Cross Product Rule,

(p + 4)(p + 5) = 6

p2 + 5p + 4p + 20 = 6

p2 + 9p + 20 = 6

p2 + 9p + 20 - 6 = 0

p2 + 9p + 14 = 0

(p + 2) (p + 7) = 0

p = -2 or p = -7

Problem 14 :

Solution:

Use Cross Product Rule,

(n + 1)(n - 4) = 50

n2 - 4n + n - 4 = 50

n2 - 3n - 4 = 50

n2 - 3n - 4 - 50 = 0

n2 - 3n - 54 = 0

(n - 9)(n + 6) = 0

n = 9 or n = -6

## Recent Articles

1. ### Finding Range of Values Inequality Problems

May 21, 24 08:51 PM

Finding Range of Values Inequality Problems

2. ### Solving Two Step Inequality Word Problems

May 21, 24 08:51 AM

Solving Two Step Inequality Word Problems